The main causes of soil contamination with heavy metals (Pb, Cd, Hg) on the northeastern slope of the Lesser Caucasus of the Republic of Azerbaijan - Mammadov, Adik; Abdullayev, Asadulla (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Problems Statement and Purpose. The subject of discussion is soil pollution - a type of anthropogenic degradation in which the content of chemicals in soils subject to anthropogenic impact exceeds the natural regional background level. The population of the earth is growing rapidly. Population growth requires food supply and meeting their consumption. At this time, the environment is polluted. Industry and agriculture especially cause soil pollution. For this reason, its research is an urgent issue. We also analyzed environmental pollution during the study. The research area is located in the Lesser Caucasus physical-geographic region, where the most important industrial enterprises in our country are located. The region is located in the western part of Azerbaijan, in an area rich in minerals. Both non-ferrous and ferrous metals are rich here. The natural conditions are also favorable for the development of industry in the area. Its richness in mineral deposits makes large-scale research of the area relevant. Therefore, our research is dedicated to the actual topic. Data and Methods. For analysis, soil samples were taken from the research area and analyzed in the laboratory. Soil samples were taken from different soil types in the Lesser Caucasus. Based on the results of these analyses, comparisons were made for soil types.Then calculations were made based on mathematical and statistical methods. During the study, the results of previous studies in the area were also used. Results and Discussion. As a result of the research, the influence of man-made emissions of lead, cadmium and mercury on various soil types on the northeastern slope of the Lesser Caucasus was studied, and the mechanisms that determine the state and behavior of heavy metals in background and soils subject to contamination were investigated. Ganja aluminum plant and Dashkasan ore refining plant located in the study area play a special role in soil pollution. Conclusion. It has been noted that the excess content of certain chemicals (Pb, Hg, Cd) in the human environment (compared to natural levels) due to their receipt from anthropogenic sources has a negative impact on the environment. The process by which uncharacteristic microelements appear in the soil, characterized by a toxic effect and affecting the properties of the soil, is called soil contamination with heavy metals. It has been established that soil contamination with such chemical elements as lead, cadmium, and mercury poses a particular environmental hazard.